2019
DOI: 10.47770/ukmead.793737
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bilgiler Ders Kitaplarında Güncel Olayların Kullanım Durumu

Abstract: Sosyal bilgiler dersinde güncel olayların öğretiminde çeşitli yollar bulunmaktadır. Bu yollardan en çok tercih edileni güncel olayların sosyal bilgiler ders kitabında öğrenme alanına eklenmiş olarak öğretilmesidir. Bu araştırmada amaç, ortaokul sosyal bilgiler ders kitaplarında güncel olayların kullanımının incelenmesidir. Nitel araştırma yöntemlerinden, doküman incelemesi yöntemi kullanılan bu çalışmada doküman olarak ortaokul ders kitapları seçilmiştir. Araştırmada 2019-2020 eğitim-öğretim yılında kullanılmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It could lead to more meaningful and permanent learning via active participation in the class. Also, it improves life experiences (Durmus x, 2017; Eryılmaz, 2015;Sag˘lamgo¨nc€ u & Deveci, 2023;Vezirog˘lu, 2022). Teachers could effectively employ current issues to facilitate acquisition of course achievements by the students and to support them in the development of accurate cognitive schemes about certain concepts.…”
Section: The Aim Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It could lead to more meaningful and permanent learning via active participation in the class. Also, it improves life experiences (Durmus x, 2017; Eryılmaz, 2015;Sag˘lamgo¨nc€ u & Deveci, 2023;Vezirog˘lu, 2022). Teachers could effectively employ current issues to facilitate acquisition of course achievements by the students and to support them in the development of accurate cognitive schemes about certain concepts.…”
Section: The Aim Of the Studymentioning
confidence: 99%
“…Because students often tend to imitate the behavior of their parents when citing the news. Exchange of ideas about news would increase familial interaction (Vezirog˘lu, 2022).…”
Section: The Aim Of the Studymentioning
confidence: 99%
“…Different studies on education and media exist in the literature (Altun, 2010;Avşar, 2013;Bayer & Bulut Özek, 2021;Bendhaj, 2023;Bulger, 2023;Dolanbay, 2022;Fernandes et al, 2022;Gupta et al, 2023;Asrak Hasdemir, 2012;Kıran, 2020;Yao, 2019). Social studies textbooks have been analyzed concerning values education approaches (Ersoy & Şahin, 2012), values (Kuş et al, 2013), cultural values and ideology (Pandhiani et al, 2016), conscious consumerism (Dere & Aktaşlı, 2019), global issues (Dere & Uçar, 2020), skills (Altay, 2020), personalities (Batmaz, 2022;Osmanoğlu & Cantemür, 2020), current events (Öztürk & Veziroğlu, 2020), power and ideology (Wangdu, 2020), society and knowledge (Hansen & Puustinen, 2021), religion (Zhao, 2020), empathy (Kan & Tebiş, 2022), citizenship values and skills (Gökçınar, 2022), disadvantaged groups (Demirezen & Kaya, 2023) and geographical elements (Ersoy & Ayaydın, 2023). However, no large-scale research has examined social studies textbooks through a media lens.…”
Section: Introductionmentioning
confidence: 99%
“…The subject that comes closest to the topic of this research is "the use of current events in Social Studies education", and only three articles have been found in the literature focusing on this subject: Taşkın and Memişoğlu (2019), Öztürk and Veziroğlu (2020) and Çelik and Yıldırım (2021). These studies evaluate the usage degrees of contemporary issues in social studies textbooks with regard to class levels and learning areas.…”
Section: Introductionmentioning
confidence: 99%